If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = n + 11 Reorder the terms: 4 = 11 + n Solving 4 = 11 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 4 + -1n = 11 + n + -1n Combine like terms: n + -1n = 0 4 + -1n = 11 + 0 4 + -1n = 11 Add '-4' to each side of the equation. 4 + -4 + -1n = 11 + -4 Combine like terms: 4 + -4 = 0 0 + -1n = 11 + -4 -1n = 11 + -4 Combine like terms: 11 + -4 = 7 -1n = 7 Divide each side by '-1'. n = -7 Simplifying n = -7
| 3x-4=x+9 | | 2(4-3x)+12=7x-5(2x-7) | | -3(8k-3)=-17+2k | | 7(x-1)+3= | | 2(x-2)/3+5x=10 | | 3w-5+3w-5= | | 2(x-2)/5+5x=10 | | 240/275 | | 4x-(x^2)=0 | | 55x=1 | | 11x^2-28x-15=0 | | 25a^2+60ab+36b^2-64=0 | | 3x/5-0.5+1.9 | | (15/1)/(-3/4) | | x=180-(90-x)-4 | | 6(x+2)+10x=8x+3(x-9) | | x=180-((90-x)-4) | | 15/1/-3/4 | | x/6-x+3/5=1 | | 6x+9=9x+3 | | r+5/3=-6 | | M-12=18 | | .75y-5=-.5y+4 | | .75y-5=-.5y+5 | | -0.5=d/9 | | 9t-6-6t=7 | | y/8+4=-15 | | 3(x-6)+8=5x-2 | | 2y^2-2y=84 | | 10z-3z-2=24-2z | | 10(3x-10)=4(5x-10) | | 3x/6-(x-2)/2=(x-1)/4 |